Construction of a recombinant food-grade Lactococcus lactis expressing P23 protein of Cryptosporidium parvum - Liu, Xuehan; Deng, Lei; Li, Wei; Zhong, Zhijun; Zhou, Ziyao; Peng, Guangneng (Folia microbiologica, 2022)
Cryptosporidium parvum infects enterocytes in diverse vertebrates, including humans, and causes diarrheal illness. However, no effective drugs are available for this protozoan infection. The P23 protein of C. parvum is a protective antigen, considered a potential candidate for developing an effective vaccine against cryptosporidiosis. In this study, the complementary DNA (cDNA) of the p23 gene was subcloned to Escherichia coli DH5α, with one nucleotide difference. The constructed plasmid pNZ8149-P23 was transferred by electroporation to Lactococcus lactis NZ3900, and the recombinant L. lactis NZ3900/pNZ8149-P23 strain was screened in Elliker-medium by adding bromocresolpurple indicator. A 23-kDa protein was detected by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) after nisin induction in LM17 broth medium, suggesting that P23 protein was in the form of glycosylation. Simultaneously, an optimal induction time of 9 h was determined, and the density of OD600 = 2.7 was tested. Through western blot and indirect immunofluorescence (IIF) analysis, the immunocompetence of expressed P23 antigen was identified, and its location of release to the cell interior of recombinant L. lactis was manifested. The first report of a food-grade genetically engineered L. lactis strain expressing a P23 antigen of C. parvum is herein presented. This result provides a novel and safe utilization method of P23 against C. parvum infection.
Keywords: Pyridinolcarbamate; rekombinantní proteiny; Cryptosporidium parvum; Animals; Humans; pyridinolkarbamát; Cryptosporidiosis; Cryptosporidium; lidé; Recombinant Proteins; Lactococcus lactis; kryptosporidióza; zvířata